Effect of increased building-integrated renewable energy on building energy portfolio and energy flows in an urban district of Korea. (15th December 2019) - Song, Jeonghun; Oh, Si-Doek; Song, Seung Jin
Abstract: Renewable energy sources such as solar panels with energy storage, ground-source heat pumps, and fuel cells are increasingly being integrated into buildings to improve their sustainability. This paper investigates, for an urban area, the effects of building-integrated renewable energy on the building energy portfolio and electricity & gas flows from the grid. In this study, 403 apartment buildings and 269 non-residential buildings (with a floor area over 500 m 2 ) in a district of Seoul, Korea, are assumed to integrate renewable energy sources to satisfy the renewable energy requirements of 10% and 30% of the total energy demand, respectively. The optimal renewable energy system for each building has been obtained via Linear Programming. The optimization has been carried out based on the hourly electricity, heating, and cooling loads of every building over a 1-year period. The energy loads, in turn, have been derived from the monthly electricity and gas usage data for every building. The renewable energy portfolio for the apartment buildings consists of photovoltaics, fuel cells, and solar water heaters. About 74% of the renewable energy for apartment buildings is provided by photovoltaics. The renewable energy portfolio for the non-residential buildings consists of ground-source heat pumps and photovoltaics. About 71% of the renewable energy is provided by the ground-source heat pumps. Consequently, total electricity and gas supply from the grid to all of the buildings in the district decrease by 17% and 3%, respectively. The photovoltaics induce a large variation in power flow from the grid during the daytime (i.e., the so-called Duck curve). The annual peak power occurs in the winter mornings because electricity powered heating by ground-source heat pumps replaces gas heating, and maximum heat demand occurs in winter mornings. Highlights: Most apartment buildings adopt only photovoltaics. All non-residential buildings adopt both photovoltaics and ground-source heat pumps. Only large apartment complexes adopt fuel cells or solar water heaters. Decrease in electricity use is much higher than decrease in gas use. Total power load decreases much in the daytime and shows its peak in winter mornings.